Migrant Workers and Remittances: Issues for Asian Developing Countries - M. G. Quibria (Asian Development Review, 1986)
The sharp increase in the price of oil in 1973 led to a massive accumulation of revenues by the oil-producing countries in the Middle East and the emergence of that region as a “growth pole” within the developing world. The large-scale investment programs, especially in infrastructure, on which these countries embarked required a labor force which was far beyond their available human resources in terms of size and composition. These countries, therefore, undertook plans for the importation of foreign workers on a contractual basis to fill well-defined jobs for short periods of time. This arrangement had two advantages. First, the countries did not have to wait for their indigenous labor supply to develop. Second, they did not have to invest huge amounts in social infrastructure, since the workers – mostly single males – were hired for relatively short periods. Many Asian developing countries took advantage of this labor market and large numbers of workers emigrated to the Middle East, especially after 1975. An important feature of this migration has been its composition of predominantly lower levels of managerial and skilled workers, in contrast to the migration of highly skilled and professional people – also referred to as the “brain drain” – from developing to developed countries…